Pelaksanaan Program Tahfidz Al-Qur’an Dalam Membentuk Karakter Religius Peserta Didik - Dinda Dwi Azizah; Murniyetti Murniyetti (An-Nuha, 2023)
The purpose of this study was to find out how the implementation of the Al-Qur'an tahfidz program in shaping the religious character of students at Madrasah Aliyah Negeri (MAN) 2 Padang City, using a qualitative case study method. Data collection by interviews, observation, and documentation, then analyzed by reducing, presenting, and drawing conclusions. The validity test technique uses triangulation. The results of the study show that: first, the tahfidz program planning is prepared through procedures, namely: a) Setting goals; b) Determine success; c) Determine the person in charge; d) Arrange schedules and activities. Second, the implementation of the tahfidz al-Qur'an program is seen from the implementation process, the methods used, and the formation of religious characters such as faith and piety, honesty, hard work, discipline, and responsibility through the tahfidz Al-Qur'an program. The three evaluations for the tahfidz al-Qur'an program are mid-semester evaluations and end-semester evaluations.